2020
DOI: 10.1111/ene.14607
|View full text |Cite
|
Sign up to set email alerts
|

Biological fluid levels of iron and iron‐related proteins in Parkinson’s disease: Review and meta‐analysis

Abstract: Background and purpose Several studies suggested a role or iron in the pathogenesis or Parkinson's disease (PD), and substantia nigra iron concentrarions have been found increased in PD. However, the results on cerebrospinal (CSF) and serum/plasma iron levels in PD patients have been controversial. The aim of this systematic review and meta‐analysis was to establish the CSF and serum/plasma levels of iron and iron‐related proteins (ferritin, transferrin, lactoferrin, haptoglobin, and hepcidine) levels, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…However, there are still many questions to be answered regarding the increase in the naturally Lf levels in the PD brain. First, the expression of Lf was detected in neurons, microglia and oligodendrocytes in PD patients [ 43 ]; however, there was no significant difference in the level of Lf in the plasma/serum or even in the cerebrospinal fluid (CSF) between PD patients and controls [ 105 ]. A case-control study further suggested the existence of endogenous Lf.…”
Section: Lf In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, there are still many questions to be answered regarding the increase in the naturally Lf levels in the PD brain. First, the expression of Lf was detected in neurons, microglia and oligodendrocytes in PD patients [ 43 ]; however, there was no significant difference in the level of Lf in the plasma/serum or even in the cerebrospinal fluid (CSF) between PD patients and controls [ 105 ]. A case-control study further suggested the existence of endogenous Lf.…”
Section: Lf In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Some support for the hypothesis that Fe accumulation in the brain causes disease can be found from a study in anemic Korean older adults, who showed lower risk of developing PD [294]. On the other hand, a meta-analysis showed mildly decreased serum Fe levels in PD patients compared to controls [107]. A recent study found that in the SN of elderly individuals, oligodendroglial and astroglial cells contained the highest cellular Fe concentrations, whereas in PD, the Fe concentrations were increased in most cell types, including neurons in the SN [112].…”
Section: Iron Accumulation and Pathology In Sporadic Neurodegenerativ...mentioning
confidence: 95%
“…Parkinson Disease ↓ Fe in serum/plasma [107] ↑ Fe in substantia nigra [108,109] ↑ Fe in neurons and adjacent neuropil, microglia, perivascularly in extracellular deposits [110][111][112] Fe bound to neuromelanin in dopaminergic neurons [112,113] Alzheimer Disease ↓ Fe in serum/plasma [114][115][116] ↑ Fe in (mostly temporal) cortex, globus pallidus, caudate, putamen [117][118][119][120][121][122] ↑ Fe in amyloid plaques, microglia, along myelinated fibers [117,[123][124][125] Fe bound to amyloid partially composed of magnetite nanoparticles [126,127] Amyotrophic Lateral Sclerosis ↑ ferritin, ↓ transferrin in serum [128] ↑ Fe in liver, kidneys [129] ↑ Fe in spinal cord [130,131] ↑ Fe in motor cortex, caudate, subthalamic nucleus, globus pallidus, substantia nigra, red nucleus [132][133][134] ↑ Fe in spinal cord neuron nuclei [135] ↑ Fe in microglia in motor cortex [136] n.a.…”
Section: Macroscopic Cellular Subcellularmentioning
confidence: 99%
“…Peripheral iron metabolism, on the other hand, was generally found to be unrelated to the risk of parkinsonism. A meta-analysis of all quantitative reports of iron in the substantia nigra and biofluids in Parkinson disease concluded that cerebrospinal iron levels were non-significantly higher and serum/plasma levels somewhat lower in parkinsonism, while CSF and serum/plasma ferritin and transferrin and serum/plasma lactoferrin and haptoglobin concentrations are similar in people with Parkinson disease and controls (reviewed: Jiménez-Jiménez et al 2021 ).
Fig.
…”
Section: ‒2000: Part 1 Building a Case For Iron And Neurodegenerationmentioning
confidence: 99%